Sensitivity of Size-measure in Firm-life Cycle Theory: Total Asset vs Total Sales - Yulianto, Arief (JDM (Jurnal Dinamika Manajemen), 2022)
Using different firm size proxies in financial research produces varying empirical results. The purpose of the paper is to find out the most appropriate firm size proxy between total sales and total assets in explaining asymmetric information at each stage of the firm life cycle. Pooled data were obtained as many as 3467 observation units from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) for the 2008-2019 period. In-line functional regression analysis based on dummy percentiles was used to answer research questions. Empirical results have explained that total sales have greater goodness of fit as a proxy for firm size than total assets. The presence of asymmetric information produces debt issues as a signal of poor quality firms. Thus, many previous studies may not be robust and biased.